Real-time foul detection in football matches using machine learning techniques - Siddiqui, Bishal Sadi; Mridul, Zeeshan Ahmed; Habib, Zaki; Sakib, Ibrahim; Chowdhury, Md. Ahmarul Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.